COVID-19-Induced Refractory Symptomatic Hypocalcemia in a Patient With Parathyroid Gland Reimplantation - Crystal Tse; Ho-Man Yeung (Case Reports in Endocrinology)
Conclusion: Acute hypocalcemia strongly correlates with a profound inflammatory response in COVID-19 patients. This case corroborates the cytokine/PTH hypothesis. This patient had a high PTH sampled near the reimplanted gland but an inappropriately normal PTH from the nonimplanted arm, indicating that direct viral interaction interfering with PTH release is an unlikely mechanism. This case represents a scenario where PTH can be sampled directly from the source and this type of model could aid in the process of determining the etiology of hypocalcemia in COVID-19.